Determination of the pharmacokinetics of glycopyrronium in the lung using a population pharmacokinetic modelling approach. (December 2013) - Bartels, Christian; Looby, Michael; Sechaud, Romain; Kaiser, Guenther
<x xml:space="preserve">Abstract</x> Aims Glycopyrronium bromide (NVA237) is a once‐daily long‐acting muscarinic antagonist recently approved for the treatment of chronic obstructive pulmonary disease. In this study, we used population pharmacokinetic (PK) modelling to provide insights into the impact of the lung PK of glycopyrronium on its systemic PK profile and, in turn, to understand the impact of lung bioavailability and residence time on the choice of dosage regimen. Methods We developed and validated a population PK model to characterize the lung absorption of glycopyrronium using plasma PK data derived from studies in which this drug was administered by different routes to healthy volunteers. The model was also used to carry out simulations of once‐daily and twice‐daily regimens and to characterize amounts of glycopyrronium in systemic compartments and lungs. Results The model‐derived PK parameters were comparable to those obtained with noncompartmental analysis, confirming the usefulness of our model. The model suggested that the lung absorption of glycopyrronium was dominated by slow‐phase absorption with a half‐life of about 3.5 days, which accounted for 79% of drug absorbed through the lungs into the bloodstream, from where glycopyrronium was quickly eliminated. Simulations of once‐daily and twice‐daily administration generated similar PK profiles in the lung compartments. Conclusions The slow absorption from the lungs, together with the rapid elimination from the systemic circulation, could explain how once‐daily glycopyrronium provides sustained bronchodilatation with a low incidence of adverse effects in patients with chronic obstructive pulmonary disease. Its extended intrapulmonary residence time also provides pharmacokinetic evidence that glycopyrronium has the profile of a once‐daily drug.